The EFL Students’ Perceptions in Doing Online English Exercises by Using Quizizz at Universitas Negeri Padang - Yuni Anriani Siregar; Witri Oktavia (Universitas Negeri Padang, 2022)
This research aims to analyze students’ perceptions and difficulties in doing online English exercises by using Quizizz. The researcher used an online questionnaire and interview as the instrumentation. The researcher used cluster random sampling to choose the sample. The sample of this research consisted of 35 students of K3’2018 English Education at Universitas Negeri Padang. In this study, the researcher used descriptive quantitative as a research design. There were two aspects of perception used in this research: perceived ease of use and perceived enjoyment. Findings from data analysis show that students perceived positively both aspects. It shows that students agree that Quizizz is easy to use, easy to access, interesting and fun, and can be used in daily online English exercises. The difficulties faced by the students were duration, slow internet connection, and uncomfortable features.